PHILOSOPHICAL STUDIES AT THE BESTUZHEV COURSES - N. H. Orlova (Дискурс, 2018)
The article analyzes the formation of the philosophy teaching tradition at the Higher women's (Bestuzhev) courses. They were organized in 1878 at St. Petersburg University under the influence of ideas about the equality of men and women. The well-known University Professors delivered lectures for girl students in the same programs as for male students. It is shown that this tradition went far beyond the formal reading of philosophy and logic. Girl students participated in serious publishing projects, became full members of the St. Petersburg Philosophical Society, have been involved in teaching activities. We can talk about the academic Union, in which professors and girl students linked the idea of science. The scientific «feminine» elite was formed under the influence of brilliant Professors of St. Petersburg University.